IMPACT OF REWARD MANAGEMENT ON THE EMPLOYEE RETENTION - Riak , Dr Gabriel Alier; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
This chapter presents the background of the study, the problem statement of the study, the purpose of study, objectives of the study, significance of the study, the Subject scope of the study (geographical, Content and Time scope) and conceptual framework